Analisis Faktor-Faktor yang Mempengaruhi Keberhasilan Koperasi Wanita di Kecamatan Gianyar - Kirana, A. A. Istri Agung Ratih; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 5, Mei 2017 (pp. 677 - 919), 2017)
The purpose of this study are to determine analyze the influence directly or indirectly members, capital, and quality of human resources to the success cooperatives through participation members, difference in the success rate Women's Cooperative independent and self-sufficient, as well as how to condition the success of Women's Cooperative in District of Gianyar. Analysis technique used is descriptive statistics, path analysis, and test different. Based on analysis, members, capital, and human resources quality in partial direct and significant impact on participation members. Members directly affects the success cooperative, while the quality of human capital and has no influence on the success cooperative. Full participation members of mediation indirect influence on success members of the cooperative, while participation members a partial mediating indirect influence of capital and quality of human resources to the success cooperative. In addition, there are differences in level success of the Women's Cooperative independent and not independent.
Keywords: jumlah anggota; modal; kualitas SDM; partisipasi anggota; keberhasilan koperasi